KOMPARATIF PEMIKIRAN IMAM HAMBALI DAN IMAM SYAFI’I TERHADAP IDAH WANITA AKIBAT CERAI KHULU’ - Karuniawan, Fathony; Nuriskandar, Lalu Hendri; Hardiyatullah, Hardiyatullah (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2023)
Khulu' is one of the marriage breakers, as a result of this khulu' divorce causes another legal event, namely the provision of Idah for a woman. According to Imam Hambali's opinion that Idah khulu' is enough with 1 quru khulu' is not divorce is that Allah SWT. stipulates that there are three legal consequences of divorce after dukhul and not divorced three times, and the legal consequences are contrary to the legal consequences of khulu': The husband has the right to refer to his wife as long as she is in Idah, Divorce is three times, so it is not lawful to remarry after the woman has been divorced three times, except if she has married another man and has been mixed, Idah is three times pure. As for according to Imam Shafi'i in the book Al-Umm, Khulu is divorce, As for khulu' which is considered as divorce according to Imam Shafi'i is, when the husband accepts his wife's khulu while intending divorce without intending the amount, then this khulu is a divorce that does not give opportunity for the husband to consult, because this is a kind of buying and selling, it is not allowed for the husband to control his wife's property even the wife has more right to the property. The same is true when the husband says lafazhleisure(separate) orsaraah(dismissal), then this is also considered as divorce even if it is not intended and idah khulu' is like divorce that is 3 times quru/menstruation. The relevance of Imam Hambali's thinking at the present time where idah kulu' is enough with 1 time quru, this is supported by the increasingly advanced technology nowadays that can quickly find out whether a woman's uterus is clean or not with tools such as test packs, USG. While Imam Syafi'i, the relevance of idah khulu' in today's times is not only about cleaning the womb, but idah khulu' 3 times quru holds a health benefit for women. Keywords: Women's Iddah, Divorce Khulu'